2013
DOI: 10.4314/ijbcs.v6i6.3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock in topsoil, standing floor litter and above ground biomass in <i>Tectona grandis</i> plantation 10-years after establishment in Ile-Ife, Southwestern Nigeria

Abstract: This paper provides information on carbon stock at the habitat level in the above ground biomass (ABG), standing floor litter and soils in a 10 year-old Tectona grandis plantation following restoration of a degraded secondary forest at Obafemi Awolowo University, Ile-Ife Nigeria. Four sample plots 25 m x 25 m, two in Tectona grandis plantation and two in a nearby degraded secondary forest were studied. Soil samples were randomly collected at 0-20 cm and bulk density determined. Standing floor litter was random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
5
2
3
Order By: Relevance
“…Tree aboveground biomass per plot was estimated by the summation of the TAGB of all individual trees in the plot. The total AGB for the studied area (1512.7 tonha -1 ) was higher when compared with [25] assertion that the global AGB in tropical dry and wet forest range between 30-275 tonha -1 and 213-1173tonha -1 respectively and that recorded in Ile-Ife (54.52 tonha-1 ) and reported by [26] but was smaller when compared with other studies. [14] estimated above ground biomass to be an average 215 mg tonha -1 and 192 mg tonha -1 for undisturbed tropical forest of Asia and the world respectively and also with study carried out by [27] that the total AGB of Oluwa forest of Ondo state was 162,826.343 tonha -1 that is, 162 mg tonha -1 .…”
Section: Below Ground Cocontrasting
confidence: 57%
See 1 more Smart Citation
“…Tree aboveground biomass per plot was estimated by the summation of the TAGB of all individual trees in the plot. The total AGB for the studied area (1512.7 tonha -1 ) was higher when compared with [25] assertion that the global AGB in tropical dry and wet forest range between 30-275 tonha -1 and 213-1173tonha -1 respectively and that recorded in Ile-Ife (54.52 tonha-1 ) and reported by [26] but was smaller when compared with other studies. [14] estimated above ground biomass to be an average 215 mg tonha -1 and 192 mg tonha -1 for undisturbed tropical forest of Asia and the world respectively and also with study carried out by [27] that the total AGB of Oluwa forest of Ondo state was 162,826.343 tonha -1 that is, 162 mg tonha -1 .…”
Section: Below Ground Cocontrasting
confidence: 57%
“…E.g. 152 mg t c/ha for cocoa agroforestry in South Cameroon [28]; 66-88 mg t c/ha for rubber plantation in Cameroon [29] but however higher than the value of carbon stock recorded in Ile-Ife (28.18) reported by [26]. A total of 3331.04 ton ha -1 of CO 2 was estimated to have been sequestered in the area.…”
Section: Below Ground Comentioning
confidence: 99%
“…Data on standing crop litter in the bamboo and even in the tropics were generally lacking. Odiwe et al (2012) have pointed out that the amount of standing floor litter is influenced by the recovery from disturbance (reforestation). The variation in the litter fall production of bamboo stands compared to tree species in the secondary rainforest in this study area may be attributed to the nature of species (Borisade and Odiwe, 2018), differences in biomass production (Hosking, 2003), canopy development (Shanmughavel et al, 2001) and percentage of deciduousness (Odiwe and Muoghalu, 2003).…”
Section: Litter Fall Production Comparison In the Bamboo Stands With mentioning
confidence: 99%
“…Chavan and Rasal [34] reported total standing carbon stock for Mangifera indica to be 82.83 Mg C ha -1 in India. Odiwe et al [21] reported aboveground carbon stock in Tectona grandis plantation to be 38.33 Mg C ha -1 in Nigeria. Chittachumnonk et al [22] in their study on carbon sequestration of T. grandis plantations in Thailand reported aboveground carbon stocks of 78.15 Mg C ha -1 .…”
Section: Aboveground Carbon Stock Across Different Physiognomiesmentioning
confidence: 99%